Magnetic Properties of Magnetite Nanoparticles (Fe3O4-NPs) Coated with Mesoporous Silica by Surfactant Templated Sol-Gel Method - Izza Taib, Nurul; G. St. Pierre, Timothy; C. Woodward, Robert; J. House, Michael (International Journal of Engineering and Technology, 2019)
Here, we present the magnetic properties of silica-coated magnetite nanoparticles. We have coated 7 nm of Fe3O4 with cetyltrimethylammonium bromide (CTAB) for phase transformation from hydrophobic to hydrophilic. Core-shell structure of silica-coated magnetite nanoparticles have been obtained using surfactant templated sol-gel method. The obtained silica-coated magnetite nanoparticles were characterized by transmission electron microscopy (TEM), fourier transform infrared (FTIR) spectroscopy and superconducting quantum interference device (SQuID). The hysteresis loops of the coated particles were measured using SQuID and the results showed a superparamagnetic behavior at room temperature. The saturation magnetization (Ms) of the coated particles indicate the presence of non-magnetic surface layers resulting from the strong chemical attachment of the silica to the Fe3O4â€™s surface, also observed by FTIR spectroscopy.Â Â Â